Silicon carbide composite ceramic and preparation method thereof

By using the combination of composite silicon carbide composite ceramics with composite filler, boron carbide, additives and modified polyvinyl alcohol in the silicon carbide composite ceramics, the problem of insufficient mechanical strength and toughness of silicon carbide composite ceramics in the prior art is solved, and ceramic materials with high mechanical strength and high toughness are achieved.

CN119874374AActive Publication Date: 2025-04-25CHANG ZHOU SAI PU RUI SHENG KE JI YOU XIAN GONG SI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510087000.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing silicon carbide composite ceramics have shortcomings in improving mechanical strength and toughness, especially the agglomeration problem of graphene and the lack of heat resistance of the binder.

Method used

Combined with composite silicon carbide, composite filler, boron carbide, additives and modified polyvinyl alcohol, the composite filler is prepared by mixing silicon carbide coarse powder and fine powder with specific particle size and mass ratio, and the composite filler is prepared by hydrothermal method, and the thermal stability of polyvinyl alcohol is improved by modifying jute fibers.

Benefits of technology

It significantly improves the mechanical strength and toughness of silicon carbide composite ceramics, improves the overall density and dispersion of the material, and enhances its corrosion resistance and thermal properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of ceramics, and provides a silicon carbide composite ceramic and a preparation method thereof, the silicon carbide composite ceramic comprises the following raw materials by weight: 90-110 parts of composite silicon carbide, 10-20 parts of a composite filler, 15-25 parts of boron carbide, 5-10 parts of an auxiliary agent, 1-5 parts of modified polyvinyl alcohol, and 150-250 parts of a dispersion medium. The silicon carbide composite ceramic provided by the invention has the characteristics of high mechanical strength and high toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramics, and in particular to a silicon carbide composite ceramic and a preparation method thereof. Background Art

[0002] Silicon carbide ceramics are a kind of high-temperature structural ceramics with many excellent properties such as high wear resistance, thermal conductivity, electrical insulation, heat resistance, corrosion resistance, etc. They are widely used in machinery, electronics, petrochemical, metallurgy and other industrial fields as well as the defense industry.

[0003] However, silicon carbide is a strong covalent bond compound, and its low diffusion coefficient under high-temperature sintering conditions makes it difficult to sinter to a dense state. In addition, the fracture toughness of single-phase silicon carbide ceramics is generally low. At present, the industry tends to introduce a second phase such as boron carbide, short fibers, graphene, etc. during the batching process to obtain silicon carbide composite ceramics, while maintaining the excellent properties of silicon carbide ceramics, while further improving its mechanical strength, toughness, thermal properties and electrical conductivity.

[0004] Although silicon carbide composite ceramics have many excellent properties mentioned above compared with single-phase silicon carbide ceramics, there are still some unresolved defects. For example, although adding graphene to silicon carbide ceramics can significantly improve the toughness of the composite ceramics, graphene is still very easy to agglomerate due to the strong van der Waals force between the layers, which leads to the toughness of the composite ceramics failing to achieve the ideal effect; in addition, the heat resistance of the binders used in the preparation of silicon carbide composite ceramics, such as sodium carboxymethyl cellulose and polyvinyl alcohol, needs to be improved, which may affect the strength and toughness of the prepared ceramics.

[0005] Patent CN 107602131B discloses a silicon carbide composite ceramic. The application is a graphene-based layered silicon carbide / reaction-sintered silicon carbide composite ceramic, including the following raw material components: silicon carbide coarse powder I, silicon carbide fine powder II, graphene nanosheets, charcoal black, silicon powder, dispersant, and binder. Compared with single reaction silicon carbide ceramics, its mechanical properties are significantly improved. However, the binder selected in the application is sodium carboxymethyl cellulose, which has the defect of being unstable at high temperatures, which may cause the mechanical strength of the prepared silicon carbide composite ceramic to decrease.

[0006] Therefore, there is an urgent need in the market for a silicon carbide composite ceramic with high mechanical strength and high toughness. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention uses composite silicon carbide as the main component, and synthesizes a silicon carbide composite ceramic with composite fillers, boron carbide, additives and modified polyvinyl alcohol, which has the characteristics of high mechanical strength and high toughness.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] On one hand, the present invention provides a silicon carbide composite ceramic, which comprises the following raw materials in parts by weight: 90-110 parts of composite silicon carbide, 10-20 parts of composite filler, 15-25 parts of boron carbide, 5-10 parts of additives, 1-5 parts of modified polyvinyl alcohol, and 150-250 parts of dispersion medium.

[0010] In some embodiments of the present invention, the composite silicon carbide consists of coarse silicon carbide powder and fine silicon carbide powder.

[0011] Preferably, the mass ratio of the coarse silicon carbide powder to the fine silicon carbide powder is 1:(2-3); the average particle size of the coarse silicon carbide powder is 25-35 μm, and the average particle size of the fine silicon carbide powder is 3-8 μm.

[0012] The applicant selects silicon carbide coarse powder and silicon carbide fine powder of specific particle size and mass ratio to mix to form composite silicon carbide as the main component of silicon carbide ceramics. The fine powder can fill the large pores of the coarse powder, thereby increasing the overall density of the composite ceramics and making the silicon carbide composite ceramics have better mechanical strength.

[0013] In some embodiments of the present invention, the method for preparing the composite filler comprises the following steps:

[0014] (1) adding aluminum isopropoxide to isopropanol, heating to 75-85° C., stirring, adding a mixed solution of isopropanol and deionized water, condensing and refluxing, centrifuging, taking a precipitate, washing, and drying to obtain boehmite powder for later use;

[0015] (2) adding sulfuric acid aqueous solution to graphite powder at 0-5°C, stirring, adding potassium permanganate, stirring, stirring at 35-45°C for 1-2h, heating to 65-75°C, stirring for 20-40min, cooling to room temperature, adding deionized water, adding hydrogen peroxide aqueous solution dropwise at 75-85°C, standing, centrifuging, washing, and freeze-drying to obtain graphene oxide for later use;

[0016] (3) mixing the graphene oxide of step (2) and thionyl chloride, ultrasonically treating at 35-45° C. for 20-40 min, heating to 60-70° C., stirring for 1.5-2.5 h, cooling to room temperature, distilling under reduced pressure, adding 1,2-dichloroethane, stirring, adding 1,2-dimethylpiperidin-4-amine, ultrasonically treating, heating to 85-95° C., stirring for 1.5-2.5 h, distilling under reduced pressure, adding anhydrous ethanol, ultrasonically treating, centrifuging, washing, and drying to obtain modified graphene for later use;

[0017] (4) adding the boehmite powder of step (1) and the modified graphene of step (3) into deionized water, ultrasonicating, heating to 180-190° C., stirring for 10-11 h, centrifuging, washing, and drying to obtain a composite filler.

[0018] Wherein, in the step (2), the mass ratio of graphite powder, sulfuric acid in the sulfuric acid aqueous solution and potassium permanganate is 1:(95-100):(55-60).

[0019] In some embodiments of the present invention, in step (3), the mass ratio of graphene oxide to 1,2-dimethylpiperidin-4-amine is 1:(0.3-0.5).

[0020] Preferably, in step (3), the mass ratio of graphene oxide to 1,2-dimethylpiperidin-4-amine is 1:0.4.

[0021] In some embodiments of the present invention, in step (4), the mass ratio of modified graphene to boehmite powder is 1:(0.4-0.6).

[0022] Preferably, in step (4), the mass ratio of modified graphene to boehmite powder is 1:0.5.

[0023] In the preparation process of silicon carbide composite ceramics, adding graphene as a carbon source can effectively improve the problem of insufficient toughness of silicon carbide ceramics. However, without surface treatment, graphene still has a high possibility of agglomeration in a water-based system even with the action of a dispersing agent. The agglomerates can cause problems such as uneven structure of ceramic materials, reduced strength and toughness.

[0024] On the one hand, the applicant uses graphite powder as a raw material, synthesizes graphene oxide under the oxidation of concentrated sulfuric acid and potassium permanganate, and then uses a chlorination reagent, thionyl chloride, to activate the graphene oxide and introduce 1,2-dimethylpiperidin-4-amine, thereby increasing the amino hydrophilic group in the modified graphene structure, thereby improving the dispersibility of graphene in water, and the amino group of the introduced 1,2-dimethylpiperidin-4-amine undergoes a grafting reaction with the carboxyl group on the surface of the graphene oxide, so that the modified graphene oxide structure contains a stable amide bond, making the modified The modified graphene has good dispersibility and stability in water. Furthermore, the piperidine heterocyclic structure introduced by 1,2-dimethylpiperidin-4-amine is elastic and can reduce friction to a certain extent, making the composite filler have lubricating properties. On the other hand, the applicant uses a hydrothermal method to compound boehmite and modified graphene to obtain a composite filler. The boehmite surface has a large number of hydroxyl groups and has good corrosion resistance, which synergistically improves the dispersibility and corrosion resistance of the composite filler, thereby improving the toughness and strength of the silicon carbide composite ceramics.

[0025] In some embodiments of the present invention, the auxiliary agent is polyacrylic acid or polyethylene glycol.

[0026] In some embodiments of the present invention, the method for preparing the modified polyvinyl alcohol comprises the following steps:

[0027] 1) placing jute fiber in a sulfuric acid aqueous solution, soaking it at 55-65° C. for 1-2 hours, taking out the solid, washing it, drying it, adding it to a sodium hydroxide aqueous solution, soaking it at 20-30° C. for 1-2 hours, taking out the solid, washing it, drying it, adding it to a mixed solution of silane coupling agent KH590 and anhydrous ethanol, soaking it at 20-30° C. for 4-6 hours, taking out the solid, drying it, and obtaining modified jute fiber for later use;

[0028] 2) The modified jute fiber of step 1) and polyvinyl alcohol powder are mixed, melt-blended at 145-155° C., and hot-pressed to obtain modified polyvinyl alcohol.

[0029] Wherein, in the step 1), the mass ratio of jute fiber to the silane coupling agent in the mixed solution of silane coupling agent KH590 and anhydrous ethanol is 1:(0.2-0.4).

[0030] In some embodiments of the present invention, in step 2), the mass ratio of polyvinyl alcohol powder to modified jute fiber is 1:(0.4-0.6).

[0031] Preferably, in the step 2), the mass ratio of the polyvinyl alcohol powder to the modified jute fiber is 1:0.5.

[0032] The use of binders in the preparation of silicon carbide composite ceramics can improve the strength of the ceramic green body, improve the plasticity during the molding process, reduce cracks after sintering, and improve uniformity. Among them, polyvinyl alcohol is an environmentally friendly binder with good water solubility, but polyvinyl alcohol has poor stability at high temperatures, which makes it unable to perform well in the high-temperature environment of ceramic preparation.

[0033] The applicant selected jute fiber as the modified matrix to modify the polyvinyl alcohol powder. Jute fiber is one of the cheapest natural fibers and has good heat resistance, mechanical properties, antibacterial properties and solubility. The addition of jute fiber can limit the movement of polyvinyl alcohol molecular chains and thus improve the thermal stability of polyvinyl alcohol; further, the applicant jointly modified the jute fiber with acid, alkali and silane coupling agent KH590, thereby increasing the active groups on the surface of the jute fiber, thereby effectively improving the compatibility between the jute fiber and polyvinyl alcohol, especially the thiol group in the silane coupling agent KH590 can react with the hydroxyl group on the surface of the jute fiber, and the thiol group has a high reactivity, which can effectively improve the bonding force between the jute fiber and polyvinyl alcohol, so that the heat resistance of polyvinyl alcohol is more effectively improved, thereby playing a role in improving the strength and toughness of silicon carbide composite ceramics.

[0034] In some embodiments of the present invention, the dispersion medium is a 40-60 wt % ethanol aqueous solution.

[0035] Preferably, the dispersion medium is a 50 wt % ethanol aqueous solution.

[0036] Another aspect of the present invention further provides a method for preparing the silicon carbide composite ceramics described in the above technical solution, comprising the following steps:

[0037] S1, adding composite silicon carbide, composite filler, boron carbide and additives to a dispersion medium, ball milling, adding modified polyvinyl alcohol, ball milling, and obtaining a slurry for standby use;

[0038] S2, spray granulation, pressure molding, pre-sintering and final sintering are performed on the slurry of step S1 to obtain silicon carbide composite ceramics.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The present invention uses composite silicon carbide as the main component, and synthesizes a silicon carbide composite ceramic with composite fillers, peroxide boron carbide, additives and modified polyvinyl alcohol. Through the synergistic effect of the components, the silicon carbide composite ceramic has the characteristics of high mechanical strength and high toughness.

[0041] (2) The present invention uses graphite powder as a raw material, synthesizes graphene oxide under the oxidation action of concentrated sulfuric acid and potassium permanganate, and then uses a chlorination reagent dichlorothionyl to activate the graphene oxide and introduce 1,2-dimethylpiperidin-4-amine, thereby improving the dispersibility of graphene in water. Furthermore, the applicant uses a hydrothermal method to compound boehmite and modified graphene to obtain a composite filler, which synergistically improves the dispersibility and corrosion resistance of the composite filler, thereby playing a role in improving the strength and toughness of silicon carbide composite ceramics.

[0042] (3) The present invention uses jute fiber as a modified matrix to modify polyvinyl alcohol powder, thereby improving the thermal stability of polyvinyl alcohol. The applicant also performs a combined modification of the jute fiber with acid, alkali and silane coupling agent KH590 to increase the active groups on the surface of the jute fiber, effectively improving the bonding force between the jute fiber and polyvinyl alcohol, and more effectively improving the heat resistance of polyvinyl alcohol, thereby playing a role in improving the strength and toughness of silicon carbide composite ceramics.

[0043] (4) The silicon carbide composite ceramics prepared in the present invention have high mechanical strength and high toughness, can be widely used in ceramic materials, and have good commercial application value. DETAILED DESCRIPTION

[0044] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0045] In the following embodiments and comparative examples, except for the composite filler and modified polyvinyl alcohol, the other compound monomers and related reagents used can be purchased from the market, among which the average particle size of the coarse silicon carbide powder is 30 μm, and the average particle size of the fine silicon carbide powder is 5 μm; polyacrylic acid is purchased from Zaozhuang Changxin Chemical Co., Ltd.; polyethylene glycol is PEG 200, purchased from Shandong Baihua Chemical Co., Ltd.; polyvinyl alcohol powder is PVA 1788, purchased from Shanxi Jinyang Pharmaceutical Excipients Co., Ltd.

[0046] Preparation Example 1

[0047] The synthesis method of the composite filler A comprises the following steps:

[0048] (1) Add 5 g of aluminum isopropoxide to 20 ml of isopropanol, heat to 80° C., stir for 30 min, add a mixed solution of 10 ml of isopropanol and 1.5 ml of deionized water (the addition time is controlled to be 30 min), condense and reflux for 6 h, centrifuge, take the precipitate, wash it with anhydrous ethanol three times, and dry it at 100° C. for 15 h to obtain boehmite powder for use;

[0049] (2) At 0°C, add 100 ml of 98 wt% sulfuric acid aqueous solution to 10 g of graphite powder, stir for 1 h, add 57 g of potassium permanganate, stir for 1 h, stir at 40°C for 1.5 h, heat to 70°C and stir for 30 min, cool to room temperature, add 100 ml of deionized water, add 30 wt% hydrogen peroxide aqueous solution at 80°C until the solution turns yellow and no longer fades and no bubbles are generated, stand until natural stratification, centrifuge, wash with deionized water to pH = 7, freeze-dry at -40°C for 24 h, and obtain graphene oxide for use;

[0050] (3) 10 g of the graphene oxide obtained in step (2) was mixed with 100 ml of thionyl chloride, ultrasonicated at 40 ° C for 30 min, heated to 65 ° C, stirred for 2 h, cooled to room temperature, and distilled under reduced pressure. 50 ml of 1,2-dichloroethane was added, stirred for 1 h, 4 g of 1,2-dimethylpiperidin-4-amine was added, ultrasonicated for 30 min, heated to 90 ° C, stirred for 2 h, and distilled under reduced pressure. 60 ml of anhydrous ethanol was added, ultrasonicated for 5 min, centrifuged, washed with anhydrous ethanol 3 times, and vacuum dried at 60 ° C for 10 h to obtain modified graphene for use;

[0051] (4) 5 g of the boehmite powder of step (1) and 10 g of the modified graphene of step (3) were added to 200 ml of deionized water, ultrasonicated for 30 min, heated to 185° C., stirred for 10.5 h, centrifuged, washed with deionized water 3 times, and dried at 80° C. for 6 h to obtain composite filler A.

[0052] Preparation Example 2

[0053] The specific implementation manner of composite filler B is the same as that of composite filler A, except that in step (3), the mass of 1,2-dimethylpiperidin-4-amine is replaced with 2.7 g.

[0054] Preparation Example 3

[0055] The specific implementation manner of composite filler C is the same as that of composite filler A, except that in step (4), the mass of boehmite powder is replaced with 3.6 g.

[0056] Preparation Example 4

[0057] The synthetic method of modified polyvinyl alcohol A comprises the following steps:

[0058] 1) 5 g of jute fiber was placed in 50 ml of 0.1 wt% sulfuric acid aqueous solution, soaked at 60° C. for 1.5 h, solid was taken out, washed with deionized water for 3 times, dried at 60° C. for 24 h, added to 50 ml of 0.5 wt% sodium hydroxide aqueous solution, soaked at 25° C. for 1.5 h, solid was taken out, washed with deionized water until pH=7, dried at 60° C. for 24 h, added to 100 ml of a mixed solution of silane coupling agent KH590 and anhydrous ethanol (silane coupling agent KH590: 1.5 wt%, anhydrous ethanol: 98.5 wt%), soaked at 25° C. for 5 h, solid was taken out, dried at 60° C. for 24 h, and modified jute fiber was obtained for standby use;

[0059] 2) 5 g of the modified jute fiber prepared in step 1) and 10 g of polyvinyl alcohol powder were mixed, melt-blended at 150° C., and hot-pressed at 160° C. to obtain modified polyvinyl alcohol A.

[0060] Preparation Example 5

[0061] The specific implementation manner of modified polyvinyl alcohol B is the same as that of modified polyvinyl alcohol A, except that in step 2), the mass of the modified jute fiber is replaced with 3 g.

[0062] Example 1

[0063] A silicon carbide composite ceramic comprises the following raw materials by weight: 100 parts of composite silicon carbide, 15 parts of composite filler A, 20 parts of boron carbide, 7.5 parts of polyethylene glycol, 3 parts of modified polyvinyl alcohol A, and 200 parts of dispersion medium.

[0064] The composite silicon carbide is composed of coarse silicon carbide powder and fine silicon carbide powder, with a mass ratio of 1:2.5.

[0065] The dispersion medium is a 50 wt% ethanol aqueous solution.

[0066] The preparation method of silicon carbide composite ceramics in this embodiment includes the following steps:

[0067] S1, adding composite silicon carbide, composite filler A, boron carbide and polyethylene glycol to a dispersion medium, ball milling for 7 hours, adding modified polyvinyl alcohol A, ball milling for 13 hours, and obtaining a slurry for standby use;

[0068] S2, the slurry of step S1 is sprayed and granulated (the spray pressure is 0.2MPa, the air inlet temperature is 140°C, and the air outlet temperature is 100°C), pressure molded (the pressure is 160MPa, and the holding time is 15s), pre-sintered (in a vacuum environment, the temperature is increased to 900°C at 10°C / min, kept warm for 40min, then increased to 1800°C at 10°C / min, kept warm for 1.5min, and cooled to 600°C with the furnace), and finally sintered (the temperature is increased to 2000°C at 20°C / min, and kept warm for 1.5h) to obtain silicon carbide composite ceramics.

[0069] Example 2

[0070] A silicon carbide composite ceramic comprises the following raw materials by weight: 90 parts of composite silicon carbide, 15 parts of composite filler A, 15 parts of boron carbide, 5 parts of polyacrylic acid, 1 part of modified polyvinyl alcohol A, and 150 parts of dispersion medium.

[0071] The composite silicon carbide is composed of coarse silicon carbide powder and fine silicon carbide powder, with a mass ratio of 1:2.

[0072] The dispersion medium is a 40 wt % ethanol aqueous solution.

[0073] The preparation method of silicon carbide composite ceramics in this embodiment includes the following steps:

[0074] S1, adding composite silicon carbide, composite filler A, boron carbide and polyacrylic acid to a dispersion medium, ball milling for 6 hours, adding modified polyvinyl alcohol A, ball milling for 10 hours, and obtaining a slurry for standby use;

[0075] S2, spray granulation, pressure molding, pre-sintering and final sintering are performed on the slurry of step S1 to obtain silicon carbide composite ceramics.

[0076] The conditions for spray granulation, pressure forming, pre-sintering and final sintering are the same as those in Example 1.

[0077] Example 3

[0078] A silicon carbide composite ceramic comprises the following raw materials by weight: 110 parts of composite silicon carbide, 15 parts of composite filler A, 25 parts of boron carbide, 10 parts of polyacrylic acid, 5 parts of modified polyvinyl alcohol A and 250 parts of dispersion medium.

[0079] The composite silicon carbide is composed of coarse silicon carbide powder and fine silicon carbide powder, with a mass ratio of 1:3.

[0080] The dispersion medium is a 60 wt % ethanol aqueous solution.

[0081] The preparation method of silicon carbide composite ceramics in this embodiment includes the following steps:

[0082] S1, adding composite silicon carbide, composite filler A, boron carbide and polyacrylic acid to a dispersion medium, ball milling for 8 hours, adding modified polyvinyl alcohol A, ball milling for 15 hours, and obtaining a slurry for standby use;

[0083] S2, spray granulation, pressure molding, pre-sintering and final sintering are performed on the slurry of step S1 to obtain silicon carbide composite ceramics.

[0084] The conditions for spray granulation, pressure forming, pre-sintering and final sintering are the same as those in Example 1.

[0085] Example 4

[0086] A silicon carbide composite ceramic comprises the following raw materials by weight: 95 parts of composite silicon carbide, 10 parts of composite filler A, 17 parts of boron carbide, 6 parts of polyethylene glycol, 3 parts of modified polyvinyl alcohol A, and 180 parts of dispersion medium.

[0087] Wherein, the composite silicon carbide and the dispersion medium are the same as those in Example 1.

[0088] The preparation method of the silicon carbide composite ceramic in this embodiment is the same as that in Embodiment 1.

[0089] Example 5

[0090] A silicon carbide composite ceramic comprises the following raw materials by weight: 105 parts of composite silicon carbide, 20 parts of composite filler A, 22 parts of boron carbide, 9 parts of polyacrylic acid, 3 parts of modified polyvinyl alcohol A and 230 parts of dispersion medium.

[0091] Wherein, the composite silicon carbide and the dispersion medium are the same as those in Example 1.

[0092] The preparation method of the silicon carbide composite ceramic in this embodiment is the same as that in Embodiment 1.

[0093] Example 6

[0094] This embodiment provides a silicon carbide composite ceramic and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the composite filler B replaces the composite filler A in equal amounts.

[0095] Example 7

[0096] This embodiment provides a silicon carbide composite ceramic and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the composite filler C replaces the composite filler A in equal amounts.

[0097] Example 8

[0098] This embodiment provides a silicon carbide composite ceramic and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that modified polyvinyl alcohol A is replaced by modified polyvinyl alcohol B in equal amounts.

[0099] Comparative Example 1

[0100] This comparative example provides a silicon carbide composite ceramic and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of modified graphene is used to replace the composite filler A.

[0101] The preparation method of modified graphene is the same as that of Preparation Example 1.

[0102] Comparative Example 2

[0103] This comparative example provides a silicon carbide composite ceramic and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of boehmite powder is used to replace the composite filler A.

[0104] The preparation method of boehmite powder is the same as that of Preparation Example 1.

[0105] Comparative Example 3

[0106] This comparative example provides a silicon carbide composite ceramic and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that PVA 1788 is used to replace the modified polyvinyl alcohol A in an equal amount.

[0107] Performance Testing

[0108] The mechanical strength and toughness of the silicon carbide composite ceramics of Examples 1-8 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.

[0109] The mechanical strength of silicon carbide composite ceramics is determined by testing the flexural strength, with reference to standard GB / T 4741-1999; the toughness is determined by testing the fracture toughness, with reference to standard GB / T 23806-2009.

[0110] Table 1

[0111] Group Flexural strength(MPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Example 1 570 6.5 Example 2 565 6.0 Example 3 560 6.2 Example 4 562 6.1 Example 5 564 6.2 Example 6 545 5.4 Example 7 540 5.5 Example 8 536 5.3 Comparative Example 1 520 5.0 Comparative Example 2 517 4.8 Comparative Example 3 515 4.6

[0112] It can be seen from the data in Table 1 that the silicon carbide composite ceramics in Examples 1-5 of the present invention have good mechanical strength and toughness as a whole. Among them, Examples 6-7 changed the modification ratio of 1,2-dimethylpiperidin-4-amine and the ratio between boehmite powder and modified graphene during the synthesis of the composite filler, so that the dispersibility and stability of the composite filler were not well improved, resulting in a certain degree of decrease in the flexural strength and fracture toughness of the silicon carbide composite ceramics; Example 8 changed the ratio between modified jute fiber and polyvinyl alcohol powder in modified polyvinyl alcohol, so that the mechanical strength of polyvinyl alcohol was not well improved, which led to a decrease in the flexural strength and fracture toughness of the silicon carbide composite ceramics; Comparative Examples 1-3 respectively selected modified graphene and boehmite powder to replace the composite filler A in equal amounts and PVA 1788 to replace the modified polyvinyl alcohol A in equal amounts. The test found that the mechanical strength and toughness of the silicon carbide composite ceramics showed poor results.

[0113] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A silicon carbide composite ceramic, characterized in that: The silicon carbide composite ceramic comprises the following raw materials by weight: 90-110 parts of composite silicon carbide, 10-20 parts of composite filler, 15-25 parts of boron carbide, 5-10 parts of auxiliary agent, 1-5 parts of modified polyvinyl alcohol and 150-250 parts of dispersion medium.

2. The silicon carbide composite ceramic according to claim 1, characterized in that: The composite silicon carbide consists of coarse silicon carbide powder and fine silicon carbide powder.

3. The silicon carbide composite ceramic according to claim 1, characterized in that: The preparation method of the composite filler comprises the following steps: (1) adding aluminum isopropoxide to isopropanol, heating to 75-85° C., stirring, adding a mixed solution of isopropanol and deionized water, condensing and refluxing, centrifuging, taking a precipitate, washing, and drying to obtain boehmite powder for later use; (2) adding sulfuric acid aqueous solution to graphite powder at 0-5°C, stirring, adding potassium permanganate, stirring, stirring at 35-45°C for 1-2h, heating to 65-75°C, stirring for 20-40min, cooling to room temperature, adding deionized water, adding hydrogen peroxide aqueous solution dropwise at 75-85°C, standing, centrifuging, washing, and freeze-drying to obtain graphene oxide for later use; (3) mixing the graphene oxide of step (2) and thionyl chloride, ultrasonically treating at 35-45° C. for 20-40 min, heating to 60-70° C., stirring for 1.5-2.5 h, cooling to room temperature, distilling under reduced pressure, adding 1,2-dichloroethane, stirring, adding 1,2-dimethylpiperidin-4-amine, ultrasonically treating, heating to 85-95° C., stirring for 1.5-2.5 h, distilling under reduced pressure, adding anhydrous ethanol, ultrasonically treating, centrifuging, washing, and drying to obtain modified graphene for later use; (4) adding the boehmite powder of step (1) and the modified graphene of step (3) into deionized water, ultrasonicating, heating to 180-190° C., stirring for 10-11 h, centrifuging, washing, and drying to obtain a composite filler.

4. The silicon carbide composite ceramic according to claim 3, characterized in that: In the step (3), the mass ratio of graphene oxide to 1,2-dimethylpiperidin-4-amine is 1:(0.3-0.5).

5. The silicon carbide composite ceramic according to claim 3, characterized in that: In the step (4), the mass ratio of modified graphene to boehmite powder is 1:(0.4-0.6).

6. The silicon carbide composite ceramic according to claim 1, characterized in that: The auxiliary agent is polyacrylic acid or polyethylene glycol.

7. The silicon carbide composite ceramic according to claim 1, characterized in that: The preparation method of the modified polyvinyl alcohol comprises the following steps: 1) placing jute fiber in a sulfuric acid aqueous solution, soaking it at 55-65° C. for 1-2 hours, taking out the solid, washing it, drying it, adding it to a sodium hydroxide aqueous solution, soaking it at 20-30° C. for 1-2 hours, taking out the solid, washing it, drying it, adding it to a mixed solution of silane coupling agent KH590 and anhydrous ethanol, soaking it at 20-30° C. for 4-6 hours, taking out the solid, drying it, and obtaining modified jute fiber for later use; 2) The modified jute fiber of step 1) and polyvinyl alcohol powder are mixed, melt-blended at 145-155° C., and hot-pressed to obtain modified polyvinyl alcohol.

8. The silicon carbide composite ceramic according to claim 7, characterized in that: In the step 2), the mass ratio of the polyvinyl alcohol powder to the modified jute fiber is 1:(0.4-0.6).

9. The silicon carbide composite ceramic according to claim 1, characterized in that: The dispersion medium is a 40-60wt% ethanol aqueous solution.

10. A method for preparing the silicon carbide composite ceramic according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, adding composite silicon carbide, composite filler, boron carbide and additives to a dispersion medium, ball milling, adding modified polyvinyl alcohol, ball milling, and obtaining a slurry for standby use; S2, spray granulation, pressure molding, pre-sintering and final sintering are performed on the slurry of step S1 to obtain silicon carbide composite ceramics.

Citation Information

Patent Citations

  • A silicon carbide multiphase ceramic

    CN107602131B

  • Preparation method of graphene oxide homodisperse reinforced alumina composite material

    CN107140954A

  • Silicon carbide ceramic with high specific stiffness and preparation method thereof

    CN117105668A

  • High-temperature-resistant ceramic composite material and preparation method thereof

    CN117229059A

  • Preparation method of silicon carbide ceramic

    CN117923907A